DNA polymerase POLQ and cellular defense against DNA damage - Yousefzadeh, Matthew J. (2012)
In mammalian cells, POLQ (pol θ) is an unusual specialized DNA polymerase whose in vivo function is under active investigation. POLQ has been implicated by different experiments to play a role in resistance to ionizing radiation and defense against genomic instability, in base excision repair, and in immunological diversification. The protein is formed by an N-terminal helicase-like domain, a C-terminal DNA polymerase domain, and a large central domain that spans between the two. This arrangement is also found in the Drosophila Mus308 protein, which functions in resistance to DNA interstrand crosslinking agents. Homologs of POLQ and Mus308 are found in multicellular eukaryotes, including plants, but a comparison of phenotypes suggests that not all of these genes are functional orthologs. Flies defective in Mus308 are sensitive to DNA interstrand crosslinking agents, while mammalian cells defective in POLQ are primarily sensitive to DNA double-strand breaking agents. Cells from Polq(−/−) mice are hypersensitive to radiation and peripheral blood cells display increased spontaneous and ionizing radiation-induced levels of micronuclei (a hallmark of gross chromosomal aberrations), though mice apparently develop normally. Loss of POLQ in human and mouse cells causes sensitivity to ionizing radiation and other double strand breaking agents and increased DNA damage signaling. Retrospective studies of clinical samples show that higher levels of POLQ gene expression in breast and colorectal cancer are correlated with poorer outcomes for patients. A clear understanding of the mechanism of action and physiologic function of POLQ in the cell is likely to bear clinical relevance.